THE CONCEPT OF KHULU’ IN CONTEMPORARY ISLAMIC MARRIAGE LAW: A COMPARATIVE STUDY IN EGYPT, JORDAN, AND MOROCCO - Endah Lakona Sitakar; Sukiati Sukiati; Iwan Iwan (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2026)
This research examines the concept of khul' (wife-initiated divorce with compensation) as regulated in the personal status laws of three Arab Muslim countries: Egypt, Jordan, and Morocco. Using a comparative legal approach with qualitative-normative methods, this study analyzes how each country codifies and implements khul' in its legal framework, tracing the interplay between classical Islamic jurisprudence (fiqh), national legislation, and judicial practice. Egypt through Law No. 1 of 2000 pioneered a relatively liberal khul' regime in the Arab world by allowing courts to grant khul' without requiring the husband's consent, a formulation that triggered significant scholarly and social controversy. Jordan, through the Personal Status Law No. 61 of 1976 as amended by Law No. 36 of 2010, adopts a more Hanbali-influenced approach requiring either mutual agreement or judicial determination of harm. Morocco through the Moudawwana (Family Code) of 2004 introduces the concept of shiqaq (discord) alongside khul' as mechanisms for wife-initiated divorce, reflecting the Maliki school's jurisprudence. The findings indicate that despite their shared Islamic jurisprudential foundations, the three countries exhibit significant divergences in procedural requirements, financial implications, and judicial discretion, shaped by distinct socio-political contexts and legislative priorities. The study concludes that genuine legal reform requires not only textual codification but also robust judicial implementation mechanisms and social support systems for women navigating family dissolution.